Quivers of 3×3-exponent matrices - Dokuchaev, M.; Kirichenko, V.V.; Plakhotnyk, M. (Algebra and Discrete Mathematics, 2015)
We show how to use generating exponent matrices to study the quivers of exponent matrices. We also describe the admissible quivers of 3×3 exponent matrices.